KKN Activities to Improve Knowledge about Family in Panggung Village Kota Tegal - Sokhabah, Maeli; Bimo Restu Perwiranegara; Nia Herlina; Krisna A, Muhammad (ASEAN Journal of Empowering Community, 2023)
Establishment of Tourism Village. The problem encountered in the formation of this tourist village is the use of low done by residents to local wisdom in the village stage such as beach Pulo Kodok and Batamsari beach. So there is still a lack of outside tourists who know the local wisdom found in the village stage. Health as a problem encountered at the time of direct parachuting in the field is still a lack of public knowledge about contraceptives such as birth control from the beginning, resulting in ignorance that results in misunderstanding of birth control. It happens not only to young people but to someone who is already married.